Host-microbiota interactions: The aryl hydrocarbon receptor in the acute and chronic phases of cerebral ischemia - Fan, Xuemei; Wang, Shuai; Hu, Shuqi; Yang, Bingjie; Zhang, Hao (Frontiers in Immunology, 2022)
The relationship between gut microbiota and brain function has been studied intensively in recent years, and gut microbiota has been linked to a couple of neurological disorders including stroke. There are multiple studies linking gut microbiota to stroke in the “microbiota-gut-brain” axis. The aryl hydrocarbon receptor (AHR) is an important mediator of acute ischemic damage and can result in subsequent neuroinflammation. AHR can affect these responses by sensing microbiota metabolites especially tryptophan metabolites and is engaged in the regulation of acute ischemic brain injury and chronic neuroinflammation after stroke. As an important regulator in the “microbiota-gut-brain” axis, AHR has the potential to be used as a new therapeutic target for ischemic stroke treatment. In this review, we discuss the research progress on AHR regarding its role in ischemic stroke and prospects to be used as a therapeutic target for ischemic stroke treatment, aiming to provide a potential direction for the development of new treatments for ischemic stroke.